Are banks still a risk source for stock market? Some empirical evidences - Michele Anelli; Michele Patanè; Stefano Zedda (Journal of Risk and Financial Management, 2022)
The global financial crisis of 2008 proved that what initially appeared to be relatively small losses in the financial system can be magnified to systemic ones. The European Union debt crisis has thus revived interest in the interdependence across different markets, especially sovereign debt markets and the banking sector, and in the interlinkages among idiosyncratic and common shocks. This paper analyzes the evolution over time of the incidence of common shocks on the main Italian banking groups starting from the period of European Central Bank's Quantitative Easing program. Results show that the banking sector is no longer perceived by the markets as a common risk source, overcoming the negative picture coming from the financial crisis of 2008-2009. The analysis also suggests that the common risk is broadly affected by the ECB monetary policy, and the idiosyncratic risk is linked to the recapitalization processes.
Keywords: 650; common shock; idiosyncratic shock; relative strength; rolling regression; VECM